2013
DOI: 10.1017/jfm.2012.589
|View full text |Cite
|
Sign up to set email alerts
|

The role of large-scale vortical structures in transient convective heat transfer augmentation

Abstract: The physical mechanism by which large-scale vortical structures augment convective heat transfer is a fundamental problem of turbulent flows. To investigate this phenomenon, two separate experiments were performed using simultaneous heat transfer and flow field measurements to study the vortex-wall interaction. Individual vortices were identified and studied both as part of a turbulent stagnation flow and as isolated vortex rings impacting on a surface. By examining the temporal evolution of both the flow fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 38 publications
(50 reference statements)
4
20
0
Order By: Relevance
“…Additionally, it is of great interest that the center of the main vortices are very close to the peaks obtained in the distribution of exponent m, while the peaks of heat transfer appear closer to the centreline of the channel (y/L = 0), as forced by the rotation of each branch of the vortex. According to Hubble et al [20], high levels of convection correspond to the downwash regions of vortices and not to the location of the maximum shear stress point, which is located beneath the vortex and agrees with exponent m distribution.…”
Section: Local Exponent M Vs H Distributionssupporting
confidence: 66%
“…Additionally, it is of great interest that the center of the main vortices are very close to the peaks obtained in the distribution of exponent m, while the peaks of heat transfer appear closer to the centreline of the channel (y/L = 0), as forced by the rotation of each branch of the vortex. According to Hubble et al [20], high levels of convection correspond to the downwash regions of vortices and not to the location of the maximum shear stress point, which is located beneath the vortex and agrees with exponent m distribution.…”
Section: Local Exponent M Vs H Distributionssupporting
confidence: 66%
“…Recently, Nguyen et al (2015) have demonstrated the separation between near wall species with different Sc numbers. This separation could also happen due to the partitioning effect of the repelling WSS LCS as demonstrated in Fig 3. From a design perspective, it would be interesting to manipulate these structures to obtain a WSS pattern with a desired outcome of wall concentration/temperature distribution, in similar fashion to Hubble et al (2013), who investigated the effect of vortical structures near the boundary layer on heat transfer augmentation. Finally, the bearing of these structures on near wall transport of turbulent flows remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…PIV processing was performed using Prana (available at 'http://sourceforge.net/projects/qi-tools/'), an in-house, open-source software program which has been thoroughly validated in several publications. 6,19,34,46 First, processing was conducted using ensemble and multi-frame correlation techniques to resolve the large dynamic range in the flow fields. As described above, multi-frame correlation utilizes multiple frame separations to resolve high and low velocities.…”
Section: Piv Processing Methodologymentioning
confidence: 99%